User clustering in downlink of massive MIMO-FBMC system based on undirected interference graph - Li Ning (Journal of Shanghai Normal University (Natural Sciences), 2017)
A user clustering algorithm based on the downlink of large-scale MIMO-FBMC system is proposed.When the number of user groups and the number of users are random,the algorithm adaptively represents the correlation coefficient of the channel vector between users and users as an undirected interference graph,and the weights of edges are expressed as channel vector interference intensity between adjacent users.Then clustering is performed based on the sum of the weights of each graph and the threshold.Finally,the simulation results show that the performance of this algorithm is better than the traditional user grouping method under different number of base station antennas,which reduces the complexity of the algorithm and increases total rate of the system.